Aspectos da propagação de Stigmaphyllon blanchetii C. E. Anderson - Silva, Erisson Marques da (2016)
Among the main problems of modern agriculture weeds is very important, especially for the high adaptability, efficient use of available resources and rapid development. In sugarcane several species have been reported as weeds, but little is known about the species known popularly as rat tail (Stigmaphyllon blanchetii), especially in respect to their biology. Knowing the biology of a weed management strategies become more effective. Thus, the study aimed to study the phenology and growth-tail mouse come from vegetative propagation, as well as to the germination test of their seeds under different temperatures and luminosities. The experiment was divided into three stages corresponding to the study of phenology tubers, growth and germination. The first and second stage regarding the phenology and growth of rat tail coming from vegetative propagation and were carried out with the aim of establishing phenological phases through the use of the BBCH scale and achievement of plant biometrics from pre-established dates; the third stage was carried out germination test at different temperatures and light. These were intended to find the temperature and the quality of light ideal for the growth of the species. First the tubers were separated by weight classes: (300g to 595G) and (130g to 290g). Within each class they were planted 35 tubers in pots with a capacity of 20L, and when they found each phenological event was averaged budding. With nine plants of each weight class an experiment was conducted in a completely randomized design, where each plant represented a repetition. The evaluation periods were: 120, 150, 180, 210, 240 and 270 days after planting (DAP). The variables analyzed were: plant height (AP), Total number of sheets (NTF), number of leaves of the main stem (NFHP), number of branches (primary and secondary), number of shoots, leaf area (AF), Matter dry (+ root tuber) and shoot. All results were submitted to analysis of variance and the means compared by Tukey test at 5% probability. The results showed that tubers of class 130 to 290g are more competitive by the resources available in the environment featuring rapid initial growth coupled with the early development of biometric characteristics. The temperatures that provide the best germination to Stigmaphyllon blanchetii are constant 30 ° C and the alternating 20-30 ° C. The quality of red light and dark condition improved germination and generation of normal plants to-tail mouse.